Prevalence and determinants of multidrug-resistant uropathogenic Klebsiella species and associated antimicrobial resistance genes in Port Harcourt, Nigeria - Moore Ikechi Mike-Ogburia; Tombari Pius Monsi; Easter Godwin Nwokah (BMC Infectious Diseases)
Abstract Background The increasing prevalence of multidrug-resistant (MDR) Klebsiella species in urinary tract infections (UTIs) poses substantial challenges for effective treatment and management. This study aimed to investigate the prevalence and determinants of MDR uropathogenic Klebsiella species and associated antimicrobial resistance genes among presumptive UTI patients in Port Harcourt. Methods A cross-sectional study was conducted from March to August 2022 at the Rivers State University Medical Centre and the Rivers State University Teaching Hospital in Port Harcourt. A total of 300 presumptive UTI patients were selected using a systematic random sampling technique. Midstream urine samples were processed using standard bacteriological techniques, followed by antimicrobial susceptibility testing using the Kirby-Bauer disk diffusion method. Polymerase chain reaction (PCR) assays were performed to detect resistance genes, including blaCTX-M, blaTEM-1, blaSHV, KPC, and qnrA. Data was analysed using GraphPad Prism 9, employing descriptive and inferential statistics, with significance set at p ≤ 0.05. Results Klebsiella was isolated in 48 (16%) of the 300 samples, with 41 (85.4%) isolates classified as MDR, representing 13.7% of the total samples. High resistance rates were observed against cephalosporins (60.4 − 100%), fluoroquinolones (64.6%), amoxicillin-clavulanic acid (100%), and tetracycline (81.3%) with multiple antimicrobial resistance (MAR) indices ranging from 0.17 to 0.83. Significant determinants of MDR Klebsiella infections included female sex (aOR = 3.60; 95% CI: 1.34–10.90; p = 0.0151), pregnancy (aOR = 5.13; 95% CI: 1.97–14.04; p = 0.0010), frequent antibiotic use (aOR = 2.49; 95% CI: 1.09–5.77; p = 0.0309), and recent hospitalisation (aOR = 2.84; 95% CI: 1.14–7.01; p = 0.0230). A history of previous UTI approached statistical significance (aOR = 2.10; 95% CI: 0.91–4.79; p= 0.0786). The blaCTX-M gene was detected in all representative MDR Klebsiella isolates (100%), blaTEM-1 and blaSHV genes in 66.7% each, and the KPC gene in 44.4%. Conclusions There is a high prevalence of MDR uropathogenic Klebsiella species in Port Harcourt, associated with female sex, pregnancy, frequent antibiotic use, and recent hospitalization. The blaCTX-M gene was found to be ubiquitous. These findings emphasise the need for robust antimicrobial stewardship programs, enhanced infection control measures, and continuous surveillance to mitigate uropathogenic MDR Klebsiella species.